Failure Screening By Using Ultrasonic Tomography Testing Method - Mahzan, Shahruddin; Alanu, Azizur Rahman (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Industries routinely use ultrasonic testing, a well-established Non-destructive Testing method, to detect signs on interior surfaces. Ultrasonic testing procedures have evolved from the conventional A-Scan design, which relies on sound waves traveling in straight lines, to more complicated arrangements that let sound waves bend in both advantageous and harmful directions at a specified moment. Ultrasonic Tomography Testing was used in this work to locate and see the interior flaw of concrete construction. This study aims which to identify the internal flaw in concrete structure by using Non-Destructive Testing analysis and to visualize the steel bar in concrete structure by using Non-Destructive Testing analysis. All the operational procedures would be carried out by following the ASME V: article 1, article 4, and article 5 Code and Standard. The ultrasonic technique is advantageous for analyzing variations in homogeneity and discovering faults in internal concrete buildings, as recently shown. In general, ultrasonic testing is a valuable instrument for the assessment of concrete structures, as it permits the development of extremely accurate three-dimensional tomographic pictures of the concrete parts being evaluated and enables correct diagnosis based on the acquired data.